Dispersion of settling particles in oscillatory turbulent flow subject to deposition and re-entrainment - Mazumder, B.S.; Paul, Suvadip (European journal of mechanics, B, Fluids, 2012)
This paper presents a numerical study on the stream-wise dispersion of settling particles in an oscillatory turbulent shear flow. The dispersion process is formulated in two differential equations, one for suspension and other one for deposition. The exchange of particles between the bed and the flow is permitted. The statistical parameters viz., centroid displacement, variance and dispersion coefficient which describe the transport process satisfactorily, are determined for both suspended and deposited materials. Parameters associated with their combined distributions are also discussed. It is shown that the tendency of the silt particles towards deposition and temporary storage on the bed can profoundly effect the longitudinal dispersion process. The effect is found to depend on the rate at which deposited particles are re-entrained in the flow, bed absorbency capacity and fall velocity of the particles. For oscillatory turbulent flow, a time-varying diffusivity model is considered and comparisons are made with the time-invariant one. Numerical results show that the time-varying eddy diffusivity has a finite effect on the dispersion coefficients when the flow is oscillatory with non-zero mean.